Wild micromammal host spectrum of zoonotic eukaryotic parasites in Spain. Occurrence and genetic characterisation. Issue 5 (8th July 2022) - Vioque, Fátima; Dashti, Alejandro; Santín, Mónica; Ruiz‐Fons, Francisco; Köster, Pamela C.; Hernández‐Castro, Carolina; García, Jesus T.; Bailo, Begoña; Ortega, Sheila; Olea, Pedro P.; Arce, Fernando; Chicharro, Carmen; et al.
SUMMARY: Micromammals have historically been recognized as highly contentious species in terms of the maintenance and transmission of zoonotic pathogens to humans. Limited information is currently available on the epidemiology and potential public health significance of intestinal eukaryotes in wild micromammals. We examined 490 faecal samples, grouped into 155 pools, obtained from 11 micromammal species captured in 11 Spanish provinces for the presence of DNA from Cryptosporidium spp., Giardia duodenalis, Enterocytozoon bieneusi and Blastocystis sp. The presence of Leishmania spp. was investigated in individual spleen samples. All micromammal species investigated harboured infections by at least one eukaryotic parasite, except Apodemus flavicollis, Myodes glareolus, Sorex coronatus and Sciurus vulgaris, but the sample size for these host species was very low . Cryptosporidium spp. was the most prevalent species found (3.7%, 95% confidence interval [CI]: 2.2–5.7), followed by G. duodenalis (2.8%, 95% CI: 1.6–4.6) and E. bieneusi (2.6%, 95% CI: 1.4–4.3). All pooled faecal samples tested negative for Blastocystis sp. Leishmania infantum was identified in 0.41% (95% CI: 0.05–1.46) of the 490 individual spleen samples analysed. Sequence analyses allowed the identification of Cryptosporidium andersoni (5.9%), C. ditrichi (11.7%), C. muris (5.9%), C. parvum (5.9%), C. tyzzeri (5.9%), rat genotypes CR97 (5.9%) and W19 (5.9%), vole genotypes V (11.7%) and VII (5.9%) and Cryptosproridium spp. (35.3%) within Cryptosporidium ( n = 17). Known genotypes C (66.7%) and Peru11 (25.0%) and a novel genotype (named MouseSpEb1, 8.3%) were detected within E. bieneusi ( n = 12). None of the G. duodenalis ‐positive samples could be genotyped at the assemblage level. Molecular data indicate that wild micromammals were primarily infected by rodent‐adapted species/genotypes of eukaryotic pathogens and thereby have a limited role as a source of human infections. The presence of ruminant‐adapted species C. andersoni along with finding C. parvum is indicative of an overlap between domestic/peri‐domestic and sylvatic transmission cycles of these agents.